Bringing the Church Back In Ecclesiastical Influences on the Rise of Europe - Møller, Jørgen 1979- (2019)
Recently, political scientists and economists have redoubled their attempts to understand the "Rise of Europe." However, the role of the Catholic Church has been curiously ignored in most of this new research. The medieval West was shot through with Catholic values and institutions, and only by factoring in the Church can we understand the peculiar European development from the high Middle Ages onward. More particularly, the 11th century "crisis of church and state" set in train a series of developments that were crucial for the Rise of Europe. The Church was the main locale in which the development of representation, consent, and early bureaucratic institutions took place, and it contributed to creating, integrating, and maintaining the European multistate system. This note demonstrates that current scholarship has failed to factor in ecclesiastical influences and it shows how these gaps can be filled by a more careful reading of prior historical scholarship.